PENGARUH PERSEPSI KEGUNAAN, PERSEPSI KEMUDAHAN DENGAN NIAT MENGGUNAKAN CORETAX SEBAGAI VARIABEL MEDIASI TERHADAP KEPATUHAN PAJAK PADA WAJIB PAJAK BADAN DI KOTA MAKASSAR - Saputri A, Izzati; Mira; Indriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of perceived usefulness and perceived ease of use on tax compliance, with intention to use CoreTax as a mediating variable, among corporate taxpayers in Makassar City. A quantitative, explanatory research design was employed involving 100 corporate taxpayers registered at KPP Pratama Makassar Selatan, selected through purposive sampling. Data were analyzed using SPSS version 27 through validity, reliability, classical assumption, multiple linear regression, and Sobel tests. The results show that perceived usefulness and perceived ease of use have a positive and significant effect on the intention to use CoreTax, and that intention to use CoreTax has a positive and significant effect on tax compliance. Perceived usefulness significantly affects tax compliance through the mediation of intention to use, whereas perceived ease of use does not. The Sobel test confirms that intention to use CoreTax mediates the effect of perceived usefulness on tax compliance, but does not mediate the effect of perceived ease of use. These findings support the Technology Acceptance Model (TAM).